Serial Block-Face Scanning Electron Microscopy Reveals That Intercellular Nuclear Migration Occurs in Most Normal Tobacco Male Meiocytes - Mursalimov, Sergey; Ohno, Nobuhiko; Matsumoto, Mami; Bayborodin, Sergey; Deineko, Elena (Frontiers in Plant Science, 2021)
Serial block-face scanning electron microscopy (SBF-SEM) was used here to study tobacco male meiosis. Three-dimensional ultrastructural analyses revealed that intercellular nuclear migration (INM) occurs in 90–100% of tobacco meiocytes. At the very beginning of meiosis, every meiocyte connected with neighboring cells by more than 100 channels was capable of INM. At leptotene and zygotene, the nucleus in most tobacco meiocytes approached the cell wall and formed nuclear protuberances (NPs) that crossed the cell wall through the channels and got into the cytoplasm of a neighboring cell. The separation of NPs from the migrating nuclei and micronuclei formation were not observed. In some cases, the NPs and nuclei of neighboring cells got very close, and the gap between their nuclear membranes became invisible. At pachytene, NPs came back into their own cells. After that, the INM stopped. We consider INM a normal part of tobacco meiosis, but the reason for such behavior of nuclei is unclear. The results obtained by SBF-SEM suggest that there are still many unexplored features of plant meiosis hidden by limitations of common types of microscopy and that SBF-SEM can turn over a new leaf in plant meiosis research.